If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2x + -4 = 38 Reorder the terms: -4 + 5x + 2x = 38 Combine like terms: 5x + 2x = 7x -4 + 7x = 38 Solving -4 + 7x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 7x = 38 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = 38 + 4 7x = 38 + 4 Combine like terms: 38 + 4 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 2(2x+3)-2=4(x+1) | | -18x+2=3x | | 2(4x-6)-8=8x-20 | | -x-3x-3=9 | | -18x+4=5x | | 2x+7=2(x+6) | | 9.00+1.25m=2.75m | | (6/x+3)+(6/2x+6) | | 7+5x=67 | | 7-(2x+4)=-9 | | 2(x-8)+7=6(x+2)-3x-19 | | 4(m-5)+6(-3m-6)=-15(m+2)-5 | | 1/5q=9-2/q | | 17+5x=8(x+1) | | 5-x/3= | | 220+1/2x-12x | | -12x+3=5x | | -44+3x-10=8-7x-2 | | 9z-1-3z=-4+6z+13 | | 7y-4y-13=43.49 | | x^2-4x-2y-1=0 | | x/(2x+3)=(x-1)/(2x) | | 98=7(x+8) | | 8a=0.32 | | 17-2x-7=2-2x | | 6-6x=6x-9x-9 | | x(x-1)=x(x+1) | | 60-8x=8x | | 11y-6y-13=55.90 | | 6-24x+36y=0 | | -25+3x=-2x | | 11x-9-5=10x-4+3x |